Cognitive Stimulation Therapy in Outpatient Settings for Persons with Dementia. (17th December 2021) - Zubatsky, Max; Berg-Weger, Marla; Amick, Matthew; Blessing, Debbie; Sansone, Katelyn; Brende, Anna; lundy, Janice
Abstract: Cognitive Stimulation Therapy (CST) is a non-pharmacologic evidence-based intervention for persons living with mild to moderate dementia. This clinical intervention therapy follows a structured protocol designed to connect people with memory loss to others by providing opportunities for social engagement and group discussion of current events and a different themed activity each session. This presentation will include findings from a multi-site study of the group intervention conducted in an urban and two rural out-patient settings with community-dwelling older adults. Pre- and post-assessments captured data on cognitive function, depression, quality-of-life, and mobility. While CST is offered in over 30 countries, this is the first large-scale CST study conducted in the U.S. Implications for future practice and research will be presented.